2021
DOI: 10.24815/siele.v8i3.22543
|View full text |Cite
|
Sign up to set email alerts
|

Investigating EFL learners’ knowledge of vocabulary and idiomatic expressions in a culture-based instructional environment

Abstract: This study attempted to investigate the influences of cultural background knowledge on improving Iranian pre-intermediate EFL students’ vocabulary and idiomatic expressions. To reach this purpose, the Oxford Quick Placement Test (OQPT) was performed on 100 English as a foreign language (EFL) learners and 60 of them were selected. The selected respondents were then randomly divided into three groups: group A (Target Culture=TC), group B (Iranian Culture = IC), and group C (Culture-Free=CF). Afterwards, a vocabu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…While the students seemed to struggle in memorizing the vocabularies before because in the preliminary interview they stated the learning method from their teacher was quite monotonous, after the implementation of local culture-based material they could easily remember and maintain the vocabulary longer in their brain. This is in accordance with the theory from previous researchers which stated that implementing local culture-based material through CAR could improve students' vocabulary development and motivation in learning because students no longer thought that the learning material was monotonous (Ismail, 2019;Kristiawan et al, 2022;Namaziandost et al, 2021). Furthermore, after the treatment, the students could also easily relate the vocabulary to the local folktale story used whenever they felt like they forgot the vocabulary.…”
Section: B Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While the students seemed to struggle in memorizing the vocabularies before because in the preliminary interview they stated the learning method from their teacher was quite monotonous, after the implementation of local culture-based material they could easily remember and maintain the vocabulary longer in their brain. This is in accordance with the theory from previous researchers which stated that implementing local culture-based material through CAR could improve students' vocabulary development and motivation in learning because students no longer thought that the learning material was monotonous (Ismail, 2019;Kristiawan et al, 2022;Namaziandost et al, 2021). Furthermore, after the treatment, the students could also easily relate the vocabulary to the local folktale story used whenever they felt like they forgot the vocabulary.…”
Section: B Discussionsupporting
confidence: 88%
“…Therefore, CAR is conducted to solve this problem. Previous studies have stated that using local culture-based material through CAR could improve students' vocabulary development and students' vocabulary learning motivation (Ismail, 2019;Kristiawan et al, 2022;Namaziandost et al, 2021). However, previous studies did not specify the area which the study was conducted.…”
Section: Introductionmentioning
confidence: 99%
“…The fishery vocabulary in the Hulu dialect of Banjarese depicts the cultural wealth of these people. Cultural knowledge through the richness of distinctive vocabulary is in line with the findings of Namaziandost et al (2021). They found that cultural knowledge has a positive impact on vocabulary knowledge.…”
Section: Nosupporting
confidence: 76%
“…Locally generated books are typically designed by non-native speakers in accordance with the local curricula made available via a particular nation's Ministry of Education. These textbooks attempt to acquaint EFL and ESL students with the cultural background of the foreign language to support them in developing a cross-cultural recognition taking into account the cultures of both the mother tongue and the foreign language by providing cultural knowledge about L1 and the L2 (Namaziandost, Tavakoli, & Izadpanah, 2021).…”
mentioning
confidence: 99%
“…There is a perception that most EFL textbooks, which are typically thought of as globally produced publications, focus mostly on American and English cultural elements (Shin, Eslami, & Chen, 2011;Yuen, 2011). This means that several textbooks available in colleges and bookstores are designed only from the views of English native writers, who are monocultural; non-native speakers and their local cultures have really been neglected (Roshan, 2014;Chen, 2011;Yuen, 2011;Namaziandost, Tavakoli, & Izadpanah, 2021).…”
mentioning
confidence: 99%